Complications of botulinum toxin and fillers: A narrative review. (30th December 2019) - Kassir, Martin; Gupta, Mrinal; Galadari, Hassan; Kroumpouzos, George; Katsambas, Andreas; Lotti, Torello; Vojvodic, Aleksandra; Grabbe, Stephan; Juchems, Eva; Goldust, Mohamad
Abstract: Background: Cosmetic surgery and esthetic procedures have become a billion dollar industry owing to the ever‐growing demand of the population to stay young. The injectable treatments including fillers and botulinum toxin have become highly popular because of their quick, predictable and lasting results in the management of facial wrinkles and rejuvenation. Although these treatment modalities are relatively safe, they are associated with certain side effects. Aims: In this review, we will focus on the complications of fillers and botulinum toxin. Patients/Methods: The literature research considered published journal articles (clinical trials or scientific reviews). Studies were identified by searching electronic databases (MEDLINE and PubMed) and reference lists of respective articles. Only articles available in English were considered for this review. Results: Brow ptosis and asymmetry are common adverse effects of botulinum toxin while the most common adverse effects associated with fillers are the local injection related effects manifesting as erythema, edema, pain, and ecchymosis. Conclusion: It is important that the treating physician is well verse with the various fillers and botulinum toxin complications and their management as some of the complications can be severely debilitating.